ANALISIS MOTIVASI BELAJAR SISWA DILIHAT DARI WAKTU BELAJAR PADA MATA PELAJARAN IPS DI SMP NEGERI 40 PEKANBARU - Rezki Andika; Sri Kartikaowati; Suarman Suarman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The purpose of the study was to determine the learning motivation seen from the time of student learning on Social Science subjects. The population in this study were all students of SMP Negeri 40 Pekanbaru as many as 528 students than that resulted sample at 182 respondentby using was selected by technique error rate of 10%. Data collection using questionnaires. Data analysis used different sample differentiation test. The results showed that student studied with morning learning time was higher than the students with the noon learning time. Class Motivation Available in high category with number of 59 students (54,63%) while frequency awakening motivation class while medium category with amount 61 student (85,84%).Keywords: Learning Motivation, Study Time